Innovative Attractiveness of Structurally Perfect Diamond Single Crystals in the View of Their Purposeful Use in the Cutting-Edge Techniques of the 21st Century - Novikov, M.V.; Lisakovskiy, V.V.; Zanevskiy, O.A.; Ivakhnenko, S.A. (Science and Innovation, 2024)
The research carried out at the Institute for Superhard Materials have made it possible to determine regularities of carbon phase transformations and transfer in metal solvents and to create methods for growing large-size structurally perfect diamond single crystals. The results of research underlay a basis for a diamond production technology to be used in electronics, manufacture of laser equipment and drilling tools, and in precision machining. The use of large 6-punch high pressure equipment has allowed the researchers to develop a much more effective technique for growing diamond single crystals.